Ambidexterity, a driver to enhance small and medium enterprises' innovation autonomy. (10th May 2021) - Iturrioz-Landart, Cristina; Alcalde-Heras, Henar; Aragón-Amonarriz, Cristina
SMEs suffer from structural limitations that constrain their ability to develop innovation capacities and these constraints may affect ambidextrous strategy implementations, particularly during economic recessions. To mitigate these weaknesses, SMEs often rely on inter-firm cooperation relationships to provide resources and external sources of knowledge relevant in both exploration and exploitation. The network and organisational performance effects of ambidexterity strategy have been widely studied, but scarce research has focused on the contribution that ambidexterity linked to inter-firm cooperation strategies have on SMEs innovation capabilities over time. This longitudinal study, based on a panel dataset about innovation behaviour on 2, 150 SMEs located in Spain's Basque Country during recession periods (2009-2013), verifies how ambidexterity, together with external collaboration strategy, reinforces SMEs innovation autonomy.